2019
DOI: 10.1177/0300060519825983
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic values of matrix metalloproteinases in ovarian cancer

Abstract: Objective: To investigate the prognostic significance of 23 matrix metalloproteinase (MMP) genes in patients diagnosed with ovarian carcinoma. Methods: The prognostic significance of 23 MMP genes in patients diagnosed with ovarian carcinoma was investigated using the Kaplan-Meier plotter (KM plotter), which uses the gene expression data and overall survival information of patients with ovarian cancer that were downloaded from the Gene Expression Omnibus, Cancer Biomedical Informatics Grid and The Cancer Genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 30 publications
4
58
0
Order By: Relevance
“…Notably, we observed that MMP25 was the only one gene that not only significantly expressed compared to the normal tissues but also played a significant role in the survival outcome of head and neck cancer patients by analysis of Kaplan-Meier method and univariate Cox proportional hazards regression. Likewise, recent evidence also revealed that high MMP25 expression levels were correlated with a better overall survival in ovarian cancer (22). Clinicopathological features from TCGA cohort of head and neck cancer showed that high levels of MMP25 expression were correlated with patients' clinical stages in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Notably, we observed that MMP25 was the only one gene that not only significantly expressed compared to the normal tissues but also played a significant role in the survival outcome of head and neck cancer patients by analysis of Kaplan-Meier method and univariate Cox proportional hazards regression. Likewise, recent evidence also revealed that high MMP25 expression levels were correlated with a better overall survival in ovarian cancer (22). Clinicopathological features from TCGA cohort of head and neck cancer showed that high levels of MMP25 expression were correlated with patients' clinical stages in our study.…”
Section: Discussionsupporting
confidence: 83%
“…MMP2 and MMP9, members of the MMP family, have been reported to drive metastasis in various cancer types, including pancreatic, hepatocellular and lung cancers (49). The upregulation of MMP2 and MMP9 is associated with poor prognosis in patients with ovarian and breast cancers (50,51). Furthermore, it has been reported that MMP2 and MMP9 promote the migration and invasion of cancer cells via regulation of the ERK signaling pathway (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) serve as the proteolytic enzymes of ECM relying on zinc, which is commonly used by cells via migration. MMP-2 and MMP-9 have closely been linked to the invasion of various malignancies [22,23]. Hence, we investigated MMP-2 and MMP-9 translations to assess the contribution of miR-145-5p to EOC invasion.…”
Section: Mir-223 Prohibited Eoc Cell Migrationmentioning
confidence: 99%